Expanding and quantifying the crystal chemistry of the flexible ligand 15aneN5. Issue 6 (19th January 2022) - Shircliff, Anthony D.; Allbritton, Elisabeth M. A.; Davilla, Dustin J.; Gorbet, Michael-Joseph; Jones, Donald G.; Tresp, David S.; Allen, Michael B.; Shrestha, Alina; Burgess, Gwendolyn E.; Eze, John I.; Fernandez, Andrea T.; Ramirez, Daniel; et al.
Abstract : 15aneN5 is structurally characterized complexed to Cr 3+, Mn 3+, Fe 3+, Co 3+, and Cu 2+ for the first time. Ru 3+ complexation yields a Ru 2+ diimine structure. A geometric factor quantifies the coordination geometry of the ligand in its complexes. Abstract : Tetraazamacrocycles have been very extensively exploited as transition metal ligands for a variety of purposes, including catalysis, medical imaging, pharmaceuticals, etc. However, the pentaazamacrocycles are much less commonly used for similar purposes because of poor availability, difficulties in their synthesis, and less well-known metal coordination properties. 1, 4, 7, 10, 13-pentaazacyclopentadane (15aneN5 ) was initially synthesized by a published synthetic route, which we simplified and shortened with minimal drop in yield. Eight different transition metal complexes were made using typical complexation methods. X-ray crystallography of multiple novel complexes yielded insight into the flexibility in coordination geometry of this interesting macrocycle as well as the first crystal structures of 15aneN5 with Cr 3+, Mn 3+, Fe 3+, Co 3+, Cu 2+, and Ru 2+ . A parameter to quantify the coordination geometry adopted by the ligand was devised and applied to all known crystal structures of its metal complexes. Finally, oxidation of 15aneN5 to a novel diimine macrocycle was observed during complexation with ruthenium.